(untitled) (PANGEEA, 2025)
Through this paper we want to show the ways in which we can exploit the CAD data model in the GIS environment. Knowing that in the GIS environment we also work with vector graphics in addition to raster graphics, it is visible the resemblance to computer-aided design (CAD), the editing aspects of digital geometry being similar. On the other hand, it is known that these formats that contain vector graphics and are accepted as a global exchange standard (DXF, DWG - promoted by AutoCAD / Autodesk) or (DGN - promoted by MicroStation / Bentley) can be an important primary source for processes and modelling highlighted on GIS platforms. The basic idea of the paper is created on the CAD model’s residence in the native environment on the one hand, but also its relocation in the GIS environment, demonstrating portability through import-export operations.